2014
DOI: 10.1007/s11064-014-1458-0
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanoparticles Stimulate Glycolytic Flux and Increase the Cellular Contents of Glutathione and Metallothioneins in Cultured Astrocytes

Abstract: Copper oxide nanoparticles (CuO-NPs) are frequently used for industrial or medical applications and are known for their high toxic potential. As little is known so far on the consequences of an exposure of brain cells to such particles, we applied CuO-NPs to cultured primary rat astrocytes and investigated whether such particles affect cell viability and alter their metabolic properties. Astrocytes efficiently accumulated CuO-NPs in a time- and concentration-dependent manner. The cells remained viable during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…This produces a targeted effect proven to be beneficial in animal models of conditions such as stroke and ALS, where neuroinflammation is strongly related to increased oxidative stress ( Roberts et al, 2014 ; Huuskonen et al, 2017 ). Copper-induced increases in microglial and astrocytic Mt1 expression have been reported by others ( Agullo et al, 1998 ; Bulcke and Dringen, 2015 ) and are now confirmed by the current report. This increase indicates copper dissociation from Cu II (atsm).…”
Section: Discussionsupporting
confidence: 93%
“…This produces a targeted effect proven to be beneficial in animal models of conditions such as stroke and ALS, where neuroinflammation is strongly related to increased oxidative stress ( Roberts et al, 2014 ; Huuskonen et al, 2017 ). Copper-induced increases in microglial and astrocytic Mt1 expression have been reported by others ( Agullo et al, 1998 ; Bulcke and Dringen, 2015 ) and are now confirmed by the current report. This increase indicates copper dissociation from Cu II (atsm).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, treatments which increase the GSH concentration in astrocytes should lead to an increase in the rate of cellular GSH export. This has been confirmed for astrocytes that contained higher GSH contents due to a pre-incubation with ammonium [90], arsenate [89], arsenite [91], cadmium chloride [89,91], copper chloride [89,92], copper oxide nanoparticles [93], nitric oxide [94] or with fibroblast growth factor 1 and tertiary butyl hydroquinone [95].…”
Section: Gsh Redox Cyclingmentioning
confidence: 68%
“…3d). This enzyme is expressed and active in Acrylonitrile [157] Ammonium [90,158] Anethole dithiolethione [159] Arsenite [91] Arsenate [89] Cadmium chloride [89,91] Catalpol [160] Copper chloride [89,92] Copper oxide nanoparticles [93] Curcumin Thyroid hormone [169] This [78][79][80]. In addition to Mrp1, astrocytes express a number of other Mrps and other potential GSH exporters in culture and in vivo [43, [81][82][83][84][85][86], but the contribution of these transporters in astrocytic export processes remains to be elucidated.…”
Section: Gsh Redox Cyclingmentioning
confidence: 99%
“…Intracellular storage of Cu is known to be regulated by MTs (Suzuki et al, 2002 ; Tapia et al, 2004 ; Ogra et al, 2006 ). Multiple lines of evidence show that the elevated expression of MTs is the cell’s response to the excess cellular Cu in order to protect the cells against the cytotoxicity induced by redox active Cu ions (Hidalgo et al, 1994 ; Dincer et al, 1999 ; Haywood and Vaillant, 2014 ; Bulcke and Dringen, 2015 ). It is therefore possible that the observed increase in MTs expression in the SVZ may be a consequence of age-related Cu increase in the body; yet it remains difficult to explain why the MTs expression was reduced in the CP where in fact Cu levels were increased with age.…”
Section: Discussionmentioning
confidence: 99%